IMPLEMENTATION OF CRIMINAL SANCTIONS AGAINST CHILDREN WHO COMMIT CRIMINAL OFFENSES - Suwardana, Rudi; Arif Sahlepi, Muhammad; Zarzani, T. Riza (Universitas Efarina, 2024)
This research examines the juvenile criminal justice system in Indonesia, particularly in relation to the implementation of criminal sanctions against children involved in criminal acts. Using library research methods, this study explores various relevant literature and legal documentation to understand the approach taken in handling cases of children in conflict with the law. This research found that there is a tendency to prioritize restorative justice and diversion, which aims to reintegrate children into society without involving formal court processes. Diversion, as an alternative case resolution, allows children to avoid social stigma and long-term legal consequences that can hinder their personal development. The main focus is on rehabilitation and reintegration, taking into account psychosocial and environmental conditions that influence children's behavior. The research results show the need for a more holistic approach in the juvenile criminal justice system that is not only oriented towards punishment, but also towards recovery and development of children as individuals.